The Dynamics of Color: Trauma, Violence, and the Aesthetics of Suffering in Han Kang’s The White Book - Farooqi, Hafiz Kamran; Kayani, Taimur; Nasir, Abdul Rehman (Annals of Human and Social Sciences, 2025)
This paper examines trauma, violence, and the aesthetics of suffering in The White Book by Han Kang, focusing on the complexities of personal and historical trauma within South Korean culture. It explores the symbolic use of white imagery – objects and photographs – as representations of socio-political and psychological themes. Using a qualitative approach and Judith Herman’s trauma recovery framework, the study investigates the novel’s meditative and fragmented narrative, analyzing how metaphors, symbolism, and imagery articulate both individual and collective trauma. The narrator’s journey reflects the transformation of trauma, revealing how trauma impacts identity and memory across generations. White serves as a powerful metaphor for both mourning and renewal, signifying loss while also suggesting healing. The paper argues that literature, particularly South Korean fiction, can facilitate trauma recovery by restoring confidence, rebuilding trust, and fostering societal reconnection. It concludes by encouraging further interdisciplinary inquiry into trauma, memory, and identity in literature, particularly within the context of Korean cultural and historical narratives.